A historical and historiographical commentary on Cassius Dio's Roman History book 57.1-17.8 - Mallan, C (2015)
This thesis is a historical and historiographical commentary on Book 57 (Chs. 1-17.8) of Cassius Dio's Roman History. It comprises two sections, an Introduction followed by the Commentary itself. The introduction is sub-divided into three chapters. The first of these introductory chapters (The Roman Historian at Work) presents a discussion of the historical material available for Dio's Tiberian narrative, and a discussion of the factors which were instrumental in Dio's writing and shaping his narrative of the reign of Tiberius. The second chapter (Dio on Tiberius) is an analysis of Dio's portrayal of Tiberius and of the historian’s understanding of Tiberius in the historical context of the early Principate. These chapters are followed by some brief Notes on the Text of Book 57, which considers the manuscript tradition of Book 57, and comments on portrayal of the reign of Tiberius in the Dionian tradition, and in particular the Excerpta Constantiniana, Xiphilinus, and Zonaras. The second part of the thesis, the commentary, presents an analysis of Dio's narrative from both historical and historiographical perspectives.